Pengembangan Modul Pelatihan Harmonisasi Hubungan Sekolah-Masyarakat untuk Meningkatkan Kemampuan Kolaborasi Progresif di SD Negeri Inpres Harapan - Vilia Dechressya Tomatala; Sophia Tri Satyawati; Bambang Ismanto (Attractive : Innovative Education Journal, 2026)
The purpose of this study is to develop the "Para-para Harmoni" Training Module to improve progressive collaboration between the school and parents at SD Negeri Inpres Harapan. This Research and Development (R&D) Level 3 project adopted the ADDIE framework. Data were collected through interviews, observations, questionnaires, and tests, validated via expert judgment. Analysis involved descriptive percentage statistics and the non-parametric Wilcoxon Signed Rank Test. The results indicate: 1) School-community collaboration was initially reactive and administrative with 30% communication dissonance; 2) Harmonization challenges stemmed from relational trauma after the February 2025 incident, yet significant sociocultural opportunities exist in the Helai Mbai (togetherness) philosophy and He-Para (circular dialogue) space as Sentani social capital; and 3) The module is proven: a) Highly Valid based on expert validation (97.34%), b) Highly Practical based on parent responses (95%), and c) Significantly Effective in enhancing educators' progressive collaboration skills per Wilcoxon test (p = 0.002), with average scores rising from 82.00 to 94.00. This research implies the establishment of humanistic mediation standards for primary education in Papua.